Modeling the TESS Light Curve of Ap Si Star MX TrA - Yury Pakhomov; Ilya Potravnov; Anna Romanovskaya; Tatiana Ryabchikova (Universe)
The TESS light curve of the silicon Ap star MX TrA was modeled using the observational surface distribution of silicon, iron, helium, and chromium obtained previously with the Doppler Imaging technique. The theoretical light curve was calculated using a grid of synthetic fluxes from line-by-line stellar atmosphere models with individual chemical abundances. The observational TESS light curve was fitted by a synthetic one with an accuracy better than 0.001 mag. The influence of Si and Fe abundance stratification on the amplitude of variability was estimated. Also, the wavelength dependence of the photometric amplitude and phase of the maximum light was modeled showing the typical Ap Si star behavior with increased amplitude and anti-phase variability in far ultraviolet caused by the flux redistribution.